2018
DOI: 10.1080/20009666.2018.1521245
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin and Cardiovascular disease- results of the CANVAS trial

Abstract: Canagliflozin is a new novel oral antidiabetic agent belonging to the class of sodium–glucose co-transporter 2 (SGLT2) inhibitors, inhibiting glucose reabsorption in the proximal tubule, leading to increased urinary glucose excretion and subsequently to reduction in plasma glucose concentration, in individuals with hyperglycemia. Before the approval of canagliflozin by the Food and Drug Administration (FDA) in 2013, a pair-wise meta-analyses of trials involving canagliflozin did not differ from control in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…A new group of antidiabetic drugs, sodium-glucose cotransporter 2 inhibitors (SGLT2is), has recently been shown to significantly improve the prognosis in high-risk cardiovascular (CV) patients with type 2 diabetes. The CV outcomes of SGLT2is (empagliflozin, canagliflozin and dapagliflozin) have been evaluated in, among others, three randomised clinical trials: Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME), Canagliflozin Cardiovascular Assessment Study (CANVAS) and Dapagliflizin Effect on Cardiovascular Events Thrombosis in Myocardial Infarction 58 (DECLARE-TIMI 58) [1][2][3][4][5][6][7][8][9][10]. The first and thus groundbreaking EMPA-REG OUTCOME study showed that the use of empagliflozin in patients with type 2 diabetes and a high CV risk reduced CV mortality by 38%, without significantly reducing the number of non-fatal myocardial infarctions and strokes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A new group of antidiabetic drugs, sodium-glucose cotransporter 2 inhibitors (SGLT2is), has recently been shown to significantly improve the prognosis in high-risk cardiovascular (CV) patients with type 2 diabetes. The CV outcomes of SGLT2is (empagliflozin, canagliflozin and dapagliflozin) have been evaluated in, among others, three randomised clinical trials: Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME), Canagliflozin Cardiovascular Assessment Study (CANVAS) and Dapagliflizin Effect on Cardiovascular Events Thrombosis in Myocardial Infarction 58 (DECLARE-TIMI 58) [1][2][3][4][5][6][7][8][9][10]. The first and thus groundbreaking EMPA-REG OUTCOME study showed that the use of empagliflozin in patients with type 2 diabetes and a high CV risk reduced CV mortality by 38%, without significantly reducing the number of non-fatal myocardial infarctions and strokes [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Previous trials have confirmed beneficial clinical effects of using SGLT-2 inhibitors in cardiovascular diseases [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Their nephroprotective effect has also been confirmed both in patients with and without diabetes [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 92%
“…Their nephroprotective effect has also been confirmed both in patients with and without diabetes [ 21 , 22 ]. There have been many randomised clinical trials to assess the cardiovascular outcomes of SGLT-2 inhibitors (empagliflozin, canagliflozin and dapagliflozin), including the Canagliflozin Cardiovascular Assessment Study (CANVAS), the Dapagliflozin Effect on Cardiovascular Events Thrombosis in Myocardial Infarction 58 (DECLARE—TIMI 58) and the Empagliflozin Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME) [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 23 , 24 ]. These clinical trials have revealed that when SGLT-2 inhibitors were administered to patients there was a significant reduction in CV mortality.…”
Section: Introductionmentioning
confidence: 99%
“…(defined as HbA1 ≥7.0% and ≤10.5%), CVD and CV risk factors. 62 A total of 10,142 patients were enrolled and randomized to either the canagliflozin-treated group (n=5,795) or a placebo group (n=4,347). 60,61 Mean follow-up was 188 weeks.…”
Section: Sodium-glucose Cotransporter 2 Inhibitors Cardiovascular Outcome Trialsmentioning
confidence: 99%
“…Moreover, canagliflozin showed a 33% reduction in hospitalization due to HF compared with the placebo. 60,62,63 Remarkably, canagliflozin was reported to be more efficacious in individuals with a history of HF, body mass index ≥30 kg/m 2 and HbA1c ≥8%. Canagliflozin proved to have a potent renoprotective profile by reducing the presence or development of albuminuria incidents by 27% and 20%, respectively.…”
Section: Sodium-glucose Cotransporter 2 Inhibitors Cardiovascular Outcome Trialsmentioning
confidence: 99%